LEGALITAS PENGGUNAAN CRYPTOCURRENCY SEBAGAI ALAT PEMBAYARAN DI INDONESIA - Syahrul Sajidin (Arena Hukum, 2021)
AbstractCountries in the world still do not have the same nature in compiling rules related to cryptocurrency, therfore it is very important to study the legality of using cryptocurrency as a means of payment in Indonesia. This paper aims to analyze the legal protection for the society related to the use of cryptocurrency as a payment. In particular cryptocurrency has two usability functions, namely as a medium of exchange and as a commodity. As a medium of exchange, cryptocurrency has currency characteristics because it can be accepted as a means of payment within a certain scope and its value is maintained because the number of issuance is limited. But the cryptocurrency is not a legitimate and official currency because it does not have the authority to issue and regulate, manage circulation and distribution, maintain its exchange value and all these functions are carried out by the computing system so that accountability is still doubtful.Â AbstrakNegara-negara masih belum memiliki sikap yang sama dalam menyusun aturan terkait dengan cryptocurrency sehingga sangat penting dilakukan kajian tentang legalitas penggunaan cryptocurrency sebagai alat pembayaran di Indonesia. Tulisan ini bertujuanÂ untuk menganalisa perlindungan hukum penggunaan cryptocurrency sebagai alat pembayaran. Secara khusus cryptocurrency memiliki dua fungsi kegunaan yakni sebagai alat tukar dan sebagai komoditas. Sebagai alat tukar, cryptocurrency memiliki karakteristik mata uang karena dapat diterima sebagai alat pembayaran dalam lingkup tertentu dan nilainya pun terjaga karena jumlah penerbitannya terbatas. Namun cryptocurrency bukanlah mata uang sah dan resmi karena tidak memiliki otoritas yang berwenang untuk menerbitkan dan mengatur, mengelola sirkulasi dan distribusi, menjaga nilai tukarnya dan semua fungsi tersebut dilakukan oleh sistem komputasi sehingga masih diragukan pertanggungjawabannya.